Ghana's development experience 1951-65 - Seidman, Ann Willcox (Nairobi : East African Pub. House, 1978)
This book examines social and economic development Ghana from 1951 t0 1965. It first examine the inherited structure, effects of the national government's development policies; and theoretical implication of Ghana's development experience. Topics covered include: pattern of resource allocation, exports, development strategy, institutional reorgnisation; stagnation of agriculture, over-extended infrastructure, limited manufacturing sector
Includes index.
Includes bibliographical references: p. 292-300.
lje 18/04/2018
Loans
Keywords: Economic development; Ghana